The correlation of neutrophil to lymphocyte ratio with proportional crescent purpura nephritis - YU Ya; YANG Ding-ping; Yang Hong-xia; LI Xiao-li (Linchuang shenzangbing zazhi)
Objective To evaluate the correlation between neutrophil to lymphocyte ratio(NLR) and monocytes to high density lipoprotein ratio(MHR) with proportional crescent henoch-schonlein purpura nephritis(HSPN).Methods Forty-seven patients diagnosed with purpura nephritis by renal biopsy in People’s Hospital of Wuhan University from January 2016 to July 2019 were selected and divided into children group(age<18) and adult group(age≥18). According to the proportion of crescent, they were divided into non-crescent group(group C0), crescent<25% group(group C1), and crescent≥25% group(group C2). The following data of the patients were collected: neutrophil count, lymphocyte count, monocyte mount, high density lipoprotein, hypersensitive C-reactive protein(hs-CRP), blood urea nitrogen(BUN), serum creatinine(Scr), uric acid(UA), albumin(ALb), prealbumin(PA), complement C1 q, C3 and C4, IgG, IgM, IgA, IgE, 24 h urinary protein. NLR and MHR were calculated. The differences of each index between different age groups and between different proportions of crescent in HSPN were analyzed. Results The difference of hs-CRP, IgA, C4 and Scr in different age groups was statistically significant(P<0.05). There were statistically significant differences in hs-CRP, IgA, C1 q, C3, BUN and Alb among different proportions of crescent in HSPN(P<0.05). Furthermore, the differences of hs-CRP between group C0 and group C1/C2(P<0.05), IgA between group C0 and group C1(P<0.05), complement C1 q between group C1 and group C2(P<0.05), complement C3 between group C1 and group C0/C2(P<0.05), BUN and Alb levels between group C2 and group C0/C1(P<0.05) were all statistically significant. There were no statistically significant differences in PA, IgG, IgM、IgE, UA, Scr, C4 and 24 h urinary protein. Spearman correlation analysis showed that NLR had significantly positive correlation(P<0.05) with PA(r=0.299), hs-CRP(r=0.369), Scr(r=0.305), BUN(r=0.353), proportion of crescent(r=0.320). MHR exhibited significantly negative correlation with IgM(r=-0.435, P<0.05); positive correlation(P<0.05) with UA(r=0.404), BUN(r=0.296), Scr(r=0.377); and no correlation with crescent proportions. Hs-CRP was significantly positively correlated with the proportion of crescent(r=0.346, P=0.017). According to the pathological results, glomerulus were graded and ROC curve was drawn with crescent score as the classification variable. The results showed that the critical value of NLR to evaluate the crescent during HSPN was 4.60, AUC was 0.737(95% CI 0.567～0.907, P=0.036), sensitivity 62.5%, and specificity 79.5%. Conclusions In HSPN, NLR and MHR are significantly correlated with renal function, NLR is related to the proportion of crescent and hs-CRP, and Hs-CRP is related to the proportion of crescent, which indicates that NLR is a significant inflammatory immune index in HSPN. MHR as an inflammatory immune index in HSPN needs further studies.